Bradykinin‐mediated Ca2+ signalling regulates cell growth and mobility in human cardiac c‐Kit+ progenitor cells. Issue 10 (17th August 2018) - Li, Gang; Che, Hui; Wu, Wei‐Yin; Jie, Ling‐Jun; Xiao, Guo‐Sheng; Wang, Yan; Li, Gui‐Rong
Abstract: Our recent study showed that bradykinin increases cell cycling progression and migration of human cardiac c‐Kit + progenitor cells by activating pAkt and pERK1/2 signals. This study investigated whether bradykinin‐mediated Ca 2+ signalling participates in regulating cellular functions in cultured human cardiac c‐Kit + progenitor cells using laser scanning confocal microscopy and biochemical approaches. It was found that bradykinin increased cytosolic free Ca 2+ ( Ca i 2 + ) by triggering a transient Ca 2+ release from ER IP3Rs followed by sustained Ca 2+ influx through store‐operated Ca 2+ entry (SOCE) channel. Blockade of B2 receptor with HOE140 or IP3Rs with araguspongin B or silencing IP3R3 with siRNA abolished both Ca 2+ release and Ca 2+ influx. It is interesting to note that the bradykinin‐induced cell cycle progression and migration were not observed in cells with siRNA‐silenced IP3R3 or the SOCE component TRPC1, Orai1 or STIM1. Also the bradykinin‐induced increase in pAkt and pERK1/2 as well as cyclin D1 was reduced in these cells. These results demonstrate for the first time that bradykinin‐mediated increase in free Ca i 2 + via ER‐IP3R3 Ca 2+ release followed by Ca 2+ influx through SOCE channel plays a crucial role in regulating cell growth and migration via activating pAkt, pERK1/2 and cyclin D1 in human cardiac c‐Kit + progenitor cells.